Sudden Cardiac Death in Children. Part 2 - Ye.V. Pshenichnaya (Zaslavsky O.Yu., 2013)
This article deals with the dysplastic changes in musculo-valve structures of the heart, arrhythmias and conduction disorders, associated with a risk of sudden cardiac death. The diagnostic criteria for sudden cardiac death, the events of cardio-pulmonary resuscitation, prevention of life-threatening conditions in children are provided.